2003
DOI: 10.1080/02687030344000265
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging the semantic system(s)

Abstract: Background: The organisation of the semantic system is controversially discussed among cognitive scientists. Whereas some authors assume that semantic processing is amodal, others propose modality-specific semantic systems. The amodal account holds that there is a single semantic system independent of the modality of stimulus presentation and nature of the concept. The multi-modal account, on the other hand, postulates that semantic knowledge is represented in modality-specific, distinct semantic systems. Atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 63 publications
(65 reference statements)
2
14
0
Order By: Relevance
“…However, modality-specific activations were also reported in posterior brain regions when action-related conceptual properties were accessed by pictures and in anterior temporal brain regions when more complex conceptual properties were accessed by words (Bright, Moss, & Tyler, 2004; Gates & Yoon, 2005; Postler, De Bleser, Cholewa, Glauche, Hamzei, & Weiller, 2003; Sevostianov, Horwitz, Nechaev, Williams, From, & Braun, 2002; Vandenberghe, Price, Wise, Josephs, & Frackowiak, 1996; Wright et al, 2008; see also Chao, Haxby, & Martin, 1999; Tyler, Stamatakis, Bright, Acres, Abdallah, Rodd, & Moss, 2004). …”
mentioning
confidence: 95%
“…However, modality-specific activations were also reported in posterior brain regions when action-related conceptual properties were accessed by pictures and in anterior temporal brain regions when more complex conceptual properties were accessed by words (Bright, Moss, & Tyler, 2004; Gates & Yoon, 2005; Postler, De Bleser, Cholewa, Glauche, Hamzei, & Weiller, 2003; Sevostianov, Horwitz, Nechaev, Williams, From, & Braun, 2002; Vandenberghe, Price, Wise, Josephs, & Frackowiak, 1996; Wright et al, 2008; see also Chao, Haxby, & Martin, 1999; Tyler, Stamatakis, Bright, Acres, Abdallah, Rodd, & Moss, 2004). …”
mentioning
confidence: 95%
“…Among the studies using PET and fMRI, those designs that have compared lexical vs. non-lexical stimuli within the visual modality (pictures vs. written words) predominate, and have examined both basic (Sevostianov et al, 2002; Tyler et al, 2003) and superordinate processing (Vandenberghe et al, 1996; Chao et al, 1999; Moore and Price, 1999; Postler et al, 2003; Bright et al, 2004). Other recent work has utilized both auditory and visual input to compare basic level processing of verbal and non-verbal stimuli (Thierry and Price, 2006; Hocking and Price, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that many of these semantic adaptation studies found adaptation in the inferior frontal and middle temporal gyri in particular, could be interpreted as support for amodal representations, as it has been suggested that these areas underlie amodal semantic processing (e.g., Postler et al, 2003). Crucially, however, none of these prior adaptation studies attempted to test specific sensorimotor features.…”
Section: Introductionmentioning
confidence: 99%